Differences in the Hungarian households’ sport expenditures - Paár , Dávid (Applied Studies in Agribusiness and Commerce, 2013)
The paper searches the differences between the groups of Hungarian households regarding the sport expenditures’ presence in household budget and determining factors. I used the latest Household Budget Survey (HBS) of the Hungarian Central Statistical Office from 2008 which contains data of more than 7000 households. My methods were logit and probit models, where the presence of sport expenditures were explained in households’ budget. The increase of the following indicators has a positive effect onto the possibility of the sport expenditures: income status, level of education, number of the children in the household, size of settlement. The region of the household is determining the presence of the sport expenditures too, however sex of the household’s head does not play a significant role.